"We're Still Human": A Reproductive Justice Analysis of the Experiences of Criminalized Latina Mothers. Issue 1 (1st February 2023) - Crawford, Allison D.; McGlothen-Bell, Kelly; Marsh, L. Noël; Cleveland, Lisa M.
ABSTRACT: Women's incarceration has significantly increased in the United States over the past 40 years. Individuals experience numerous social, political, and economic barriers following incarceration; however, little is known about the incarceration experiences of Latina mothers in Texas, who are disproportionately affected. This study aims to examine the experiences of Latina mothers impacted by incarceration, using reproductive justice as a sensitizing lens. We used a qualitative description design and twelve Latina mothers were interviewed. We used semi-structured, individual, interviews to address the research question, "What are the experiences of Latina mothers impacted by incarceration?" We applied the reproductive justice framework to inductively sensitize the experiences with respect to the right to bodily autonomy, right to have or not have children, and right to parent in safe, sustainable environments following arrest. An overarching theme ( We're still human ) and four major themes ( I did whatever they wanted me to do; It's me against the world; Even through the pain you push through; Our voices haven't been heard loud enough ) emerged from our analysis of interview data. These themes describe experiences of discrimination, trauma, barriers, resiliency, and desires, following arrest. The findings indicate a need for more research that takes an intersectional approach; policy reform that humanizes those influenced by arrest; bridging initiatives on the individual, relational, community, and societal levels; and making probation and medication-assisted therapy services mother-centered.